Evaluating technology enhanced learning by using single‐case experimental design: A systematic review - Dayo, Nadira; Said Metwaly, Sameh; Van Den Noortgate, Wim (British journal of educational technology, 2024)
Single‐case experimental designs (SCEDs) may offer a reliable and internally valid way to evaluate technology‐enhanced learning (TEL). A systematic review was conducted to provide an overview of what, why and how SCEDs are used to evaluate TEL. Accordingly, 136 studies from nine databases fulfilling the inclusion criteria were included. The results showed that most of the studies were conducted in the field of special education focusing on evaluating the effectiveness of computer‐assisted instructions, video prompts and mobile devices to improve language and communication, socio‐emotional, skills and mental health. The research objective of most studies was to evaluate the effects of the intervention; often no specific justification for using SCED was provided. Additionally, multiple baseline and phase designs were the most common SCED types, with most measurements in the intervention phase. Frequent data collection methods were observation, tests, questionnaires and task analysis, whereas, visual and descriptive analysis were common methods for data analysis. Nearly half of the studies did not acknowledge any limitations, while a few mentioned generalization and small sample size as limitations. The review provides valuable insights into utilizing SCEDs to advance TEL evaluation methodology and concludes with a reflection on further opportunities that SCEDs can offer for evaluating TEL.Practitioner notesWhat is already known about this topic SCEDs use multiple measurements to study a single participant over multiple conditions, in the absence and presence of an intervention SCEDs can be rigorous designs for evaluating behaviour change caused by any intervention, including for testing technology‐based interventions. What this paper adds Reveals patterns, trends and gaps in the use of SCED for TEL. Identifies the study disciplines, EdTech tools and outcome variables studied using SCEDs. Provides a comprehensive understanding of how SCEDs are used to evaluate TEL by shedding light on methodological techniques. Enriches insights about justifications and limitations of using SCEDs for TEL. Implications for practice and/or policy Informs about the use of the rigorous method, SCED, for evaluation of technology‐driven interventions across various disciplines. Contributes therefore to the quality of an evidence base, which provides policymakers, and different stakeholders a consolidated resource to design, implement and decide about TEL.